2014
DOI: 10.1111/sms.12393
|View full text |Cite
|
Sign up to set email alerts
|

Hemoconcentration induced by exercise: Revisiting the Dill and Costill equation

Abstract: The Dill and Costill equation is used to estimate the exercise-induced hemoconcentration. However, this calculation requires drawing an extra whole-blood sample, which cannot be frozen and has to be analyzed with dedicate instrumentation in a relative short time. The aim of the present study was to explore the usefulness of some serum biochemical parameters to estimate hemoconcentration induced by exhaustive exercise. Fourteen healthy male subjects (19-34 years) performed a15-min running test at 110% of anaero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 20 publications
1
40
0
5
Order By: Relevance
“…In the present study, exercise significantly increased plasma albumin, what is in line with previous studies that attributed this finding to an exercise-induced reduction in plasma volume (Novosadová 1977 ; Iwato et al 1993 ; Haskell et al 1997 ; Kargotich et al 1998 ; Alis et al 2015 ). At the level of peak exercise intensity, there was no significant difference in the albumin concentration between normoxia and hypoxia.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, exercise significantly increased plasma albumin, what is in line with previous studies that attributed this finding to an exercise-induced reduction in plasma volume (Novosadová 1977 ; Iwato et al 1993 ; Haskell et al 1997 ; Kargotich et al 1998 ; Alis et al 2015 ). At the level of peak exercise intensity, there was no significant difference in the albumin concentration between normoxia and hypoxia.…”
Section: Discussionsupporting
confidence: 93%
“…Plasma albumin values were used to estimate hemoconcentration during and after the exercise as follows26: where P-albumin is in g/L and “parameter” denotes P-suPAR (ng/mL) or P-high-sensitivity CRP (µg/mL).…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, others showed that a single 20s "all-out" cycling sprint induced a significant rise in serum SPARC but that correcting circulating SPARC levels with the exercise-induced changes in plasma volume negated this effect (Songsorn et al, 2017). This finding highlights the importance of measuring hematocrit and hemoglobin levels preand postexercise to verify that the potential exercise-induced alterations in circulating protein concentrations are not due to the changes in plasma volume after exercise (Alis et al, 2015;Dill and Costill, 1974).…”
Section: Sparcmentioning
confidence: 99%